Comparison of Hip and Lumbopelvic Performance Between Chronic Low Back Pain Patients Suited for the Functional Optimization Approach and Healthy Controls. Issue 1 (1st January 2020) - Pilz, Bruna; Vasconcelos, Rodrigo A.; Teixeira, Paulo P.; Mello, Wilson; Oliveira, Isadora O.; Ananias, Juliana; Timko, Michael; Grossi, Débora B.
Abstract : Study Design: Cross-sectional study. Objective: We explored the differences between chronic low back pain (CLBP) patients suited for the functional optimization approach and healthy controls in isometric hip-strength and lumbar-endurance tests and determined classificatory cutoff values for strength and endurance tests and ratios. Summary of Background Data: To optimize the treatment effect for CLBP, some approaches have classified patients into homogeneous subgroups matched to specific treatments. We evaluated CLBP patients suited for the functional optimization approach, who seek care because they experience symptoms during activities with high physical demands, although they are relatively asymptomatic. Methods: Three hundred fifty subjects (healthy controls, 170; CLBP patients, 180) were stratified by age (18–40 and 41–65 yrs), sex, and physical activity level. The CLBP patients had an Oswestry Disability Index score < 20% and a Numeric Pain Rating Scale score < 3. The subjects underwent hip abductor, extensor, and flexor isometric strength tests; a deep abdominal function test; and lateral/frontal bridge and lumbar flexor/extensor endurance tests. Results: Relative to the healthy controls, the CLBP patients showed significantly ( P > 0.05) higher strength scores in the hip flexor and deep abdominal function tests but lower endurance in the lateral and frontal bridge and lumbar flexor and extensor tests. The cutoff values of the lumbar flexor test and the lumbar flexor/extensor, lateral bridge/lumbar flexor, frontal bridge/lumbar flexor, and hip extensor/flexor test ratios showed acceptable accuracy (AUC = 0.84, 0.82, 0.79, 0.75, and 0.73, respectively). Conclusion: In lumbopelvic and hip-performance tests, CLBP patients suited for the functional optimization approach showed differences from healthy controls. These patients could be discriminated from healthy controls on the basis of accurate cutoff values for strength and endurance tests and ratios, which should be considered in treatment decision-making when patients need to return to activities with higher physical demands. Level of Evidence: 2 Abstract : Compared with healthy controls, CLBP patients show greater hip flexor and deep abdominal scores and lower lateral/frontal bridge and lumbar flexor/extensor scores. Cutoff values for strength and endurance tests and ratios can accurately identify these patients and aid in treatment decision-making when they need to return to physically demanding activities.